Simple Oxidimetric and High Performance Liquid Chromatographic Methods for the Determination of Pantoprazole - Sankar, D.G.; Raju, M.S.M.; Murthy, T.K.; Reddy, M.V.V.N.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Three simple and sensitive methods (A, B & C) have been described for the estimation of pantoprazole (PTP) in bulk samples and pharmaceutical formulations. Methods A and B are spectrophotometric methods based on the oxidation of PTP with oxidant (potassium permanganate, MnO4-, A; ferric chloride, Fe(III), B) followed by estimation of unreacted oxidant with Fast Green FCF (FGFCF, A) or reduced form of oxidant [Fe(II)] with potassium ferricyanide ([Fe(CN)6]3-, B). Method C is a HPLC method in which C18 column with a mobile phase consisting of acetonitrile and water (60 : 40) and beclomethasone dipropionate as an internal standard were utilised. The eluents were monitored at a detection wavelength of 289 nm. The results obtained are reproducible and are statistically validated.